2005
DOI: 10.1159/000089557
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Hippocampal Estradiol-Induced N-Methyl-<i>D</i>-Aspartic Acid Binding and Ultrastructural Localization of Estrogen Receptor-Alpha

Abstract: Estradiol increases dendritic spine density and synaptogenesis in the CA1 region of the female hippocampus. This effect is specific to females, as estradiol-treated males fail to show increases in hippocampal spine density. Estradiol-induced spinogenesis in the female is dependent upon upregulation of the N-methyl-D-aspartic acid (NMDA) receptor as well as on non-nuclear estrogen receptors (ER), including those found in dendrites. Thus, in the male, the inability of estradiol to induce spinogenesis may be rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
75
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(85 citation statements)
references
References 107 publications
8
75
0
1
Order By: Relevance
“…Alongside our previous findings on the nonnuclear localization of estrogen receptor ␣ (ER␣) and ER␤ in dendritic spines (60,61), these data on GPR30 and spine localization may begin to provide an additional explanation on how E2 might modulate synaptic plasticity and non-genomic hormone effects in the hippocampus.…”
Section: Gpr30 Interacts With the Dendritic Spine Scaffold Psd-95supporting
confidence: 60%
“…Alongside our previous findings on the nonnuclear localization of estrogen receptor ␣ (ER␣) and ER␤ in dendritic spines (60,61), these data on GPR30 and spine localization may begin to provide an additional explanation on how E2 might modulate synaptic plasticity and non-genomic hormone effects in the hippocampus.…”
Section: Gpr30 Interacts With the Dendritic Spine Scaffold Psd-95supporting
confidence: 60%
“…Immunohistochemical studies using antibodies directed toward typical ERs (a or b) have shown the presence of estrogen receptors in mitochondria, endoplasmic reticulum, as well as in synaptic membranes (Blaustein et al 1992;Chen et al 2004;Revankar et al 2005;Romeo et al 2005). In these studies, the nature of the membrane-bound estrogen receptor has been proposed to resemble ERa (Razandi et al 2004;Acconcia et al 2005), and the identity of the ERb localized to membranes remains controversial (Yang et al 2004(Yang et al , 2006.…”
Section: Discussionmentioning
confidence: 99%
“…It also is likely that a consensus has been difficult because estrogen receptor (ER) localization changes with endocrine state. Thus, at proestrus, a different distribution of ERα was reported relative to other cycle stages [19,20]. Changes in ERs may also occur after estradiol treatment [21,22].…”
Section: Estrogen Estrogen Receptors and Their Distribution In Hippmentioning
confidence: 99%
“…In addition, although one may question evidence of nuclear receptors, there is evidence of cytosolic receptors in diverse areas of granule cells using electron microscopy [19,23]. It is also important to bear in mind that, depending on the endocrine state, estrogen receptors may be more or less amenable to immunocytochemical evaluation [19,20], so they could be missed. And indeed the studies that show few estrogen receptors in granule cells were conducted at a time when they were least likely to be obvious, i.e.…”
Section: B Estrogen Induces Bdnf Gene Expression By a Non-genomic Mementioning
confidence: 99%